DEMOGRAPHIC AND PATHOLOGICAL CHARACTERISTICS OF GASTRIC CARCINOMAS – A Three-Year Single Center Experience - Ognjenovic, Lj; Shumkovski, A; Trajkovski G; Bushinoska J; Nikolova D; Hadzi-Mancev D; Darko DJambaz (Macedonian Association of Anatomists, 2020)
Introduction: Despite the decline in incidence and mortality rate in recent years, gastric carcinoma (GC) remains one of the leading causes of cancer-related deaths worldwide, especially in developing countries. The aim of this study was to present the clinical and pathological characteristics of gastric carcinomas in patients from R. North Macedonia. Material and methods: One hundred and forty-nine patients with gastric carcinoma were included in the study. Sixty-one patients underwent subtotal gastric resection with lymphadenectomy, and 88 patients underwent total gastrectomy with lymphadenectomy. Tumor localization, TNM classification, grade and stage were determined for each patient. The parameters of the TNM classification (AJCC Cancer Staging 2017) were obtained from the archived histopathological reports of the Institute of Pathology in Skopje, and for the clinical stage patients’ files from the University Clinic for Abdominal Surgery in Skopje were used. Results:The most common intragastric location of gastric carcinomas was cardia in 61 (40.94%) patients, followed by antral/pyloric carcinoma location in 51 (34.23%) patients and corpus location in 37 (24.83%) patients. According to the T status (local tumor growth), more than half of the examined patients 84 (56.38%) were in T4 status of the disease. Presence of positive regional lymph nodes was detected in 113 (75.84) patients, and negative in 36 (24.16%) patients. The majority of patients that comprised the analyzed group - 81 (54.36%) had a poor differentiated gastric carcinoma, and 88 (59.06%) were in Stage III of the disease.
Keywords: gastric carcinoma; TNM stage; grade; T status